A philological study of texts in connection with aṯtart and aṯirat in the Ugaritic language - Brink, M. B.(Marthinus Beyers),1945- (Stellenbosch : Stellenbosch University, 2012)
Thesis (DLitt) -- University of Stellenbosch, 1977.